2015
DOI: 10.1002/jsfa.7160
|View full text |Cite
|
Sign up to set email alerts
|

Microbial bioconversion and processing methods enhance the phenolic acid and flavonoids and the radical scavenging capacity of Smilax china L. leaf

Abstract: BACKGROUND It has been reported that Smilax china L. leaf (SCL) provided various biological functions owing to polyphenols. The objective of the current study was to assess the enhancing effect of processing methods and microbial conversions on phenolic acid and flavonoid content and radical scavenging capacity of SCL for potential applications of diverse food products. RESULTS Targeted phenolic acid (chlorogenic acid) and flavonoids (piceid and quercetin) were identified in fresh SCL using liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In addition, several fermented foods have also been used in traditional medicine. Currently, the application of the fermentation process using microorganisms, such as fungi, yeast and bacteria has been often used to improve the beneficial effects of medicinal herbs (9)(10)(11)(12). Fermentation is known for yielding metabolites, or converting glycosylated compounds to aglycones, one of the active forms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several fermented foods have also been used in traditional medicine. Currently, the application of the fermentation process using microorganisms, such as fungi, yeast and bacteria has been often used to improve the beneficial effects of medicinal herbs (9)(10)(11)(12). Fermentation is known for yielding metabolites, or converting glycosylated compounds to aglycones, one of the active forms.…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation is known for yielding metabolites, or converting glycosylated compounds to aglycones, one of the active forms. The fermentation process is known to yield metabolites of microorganisms, or convert glycosides to aglycones (11,12,28). Nevertheless, the application of the fermentation process for the Arctium lappa fruit has been not reported to date, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, the total amount of targeted bioactive components tends to be reduced during fermentation by microbial strains including Monascus pilosus, Saccharomyces cerevisiae, Bacillus species, Bifidobacterium bifidus , and Aspergillus oryzae compared to those in fresh leaf of SC. Furthermore, antioxidant capacity was shown to be the greatest in SC leaf fermented by Aspergillus oryzae among microbial fermentation strains (Kim et al, ). Lee et al () also showed that overall sensory acceptance in SC fermented by Aspergillus oryzae was higher than any other microbial strains.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the SC tea, microbial fermentation techniques have been applied to improve its sensory qualities (Peng et al, ). Recently it was found that several processing methods for making SC tea altered targeted phenolic acids and flavonoids as well as radical scavenging capacities (Kim, Park, Yang, Suh, & Shim, ; Son & Shim, ). In detail, the total amount of targeted bioactive components tends to be reduced during fermentation by microbial strains including Monascus pilosus, Saccharomyces cerevisiae, Bacillus species, Bifidobacterium bifidus , and Aspergillus oryzae compared to those in fresh leaf of SC.…”
Section: Introductionmentioning
confidence: 99%